MODERN INSIGHTS INTO THE ROLE OF HEMORHEOLOGICAL DEVIATIONS AND FUNCTIONAL STATUS OF THE ENDOTHELIAL TISSUE IN THE PATHOGENESIS OF ACUTE INFLAMMATORY LUNG AND BRONCHIAL DISEASES AMONG CHILDREN - A.V. Mozhaev; R.R. Shilyaev; M.R. Grineva; O.A. Pakhrova ("Paediatrician" Publishers LLC, 2007)
Disorders of the endothelial tissue and hemorheology function build up one of the pathogenic bases to form the acute inflammatory abnormality of the respiratory tract among children. The overview highlights the information on the role and disorders of the erythrocyte clumping and plasticity, blood viscosity and function of the endothelial tissue as a response to the acute respiratory infections among children.Key words: endothelial dysfunction, hemorheology, hemorheological deviations, acute respiratory infections, acute bronchopulmonary diseases, children.